Pengaruh Kualitas Pelayanan Food and Beverage Department Terhadap Kepuasan Penumpang KM. Kelud PT. PELNI (Persero) - Iwa Putra Fahdiyar; Firman Syah (Destinesia : Jurnal Hospitaliti dan Pariwisata, 2021)
This study aimed to analyze The Effect of Food and Beverage Department Service Quality on Consumer Satisfaction of KM. Kelud PT. PELNI (Persero). This study used a quantitative method with a data collection technique in the form of questionnaires and literature studies. The population of this study was the class passenger of Km. Kelud PT. PELNI (Persero). The samples in this study were 73 people obtained using a total sampling method, then the data were processed by SPSS statistical analysis. The dependent Variabel in this study was service quality and the independent Variabel was customer satisfaction. The results of this study indicated that service quality had an effect on consumer satisfaction by 0.509 or 50.9% based on the coefficient of determination of 0.491 or 49.1% explained by other factors not included in this study. From the results of the T-test carried out, with the results of the analysis of 8.575 greater than 1.667 and a probability of 0.000 smaller than 0.60, it was concluded that H0 was rejected and H1 was accepted which means that the service quality Variabel (X) significantly affects the consumer satisfaction Variabel (Y).